2014
DOI: 10.1149/2.0301410jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pulse Plated Ni and NiZn Alloys

Abstract: Nickel, zinc and nickel-rich NiZn alloys were formed on platinum by galvanostatic pulse plating from aqueous sulfate baths. The alloys were formed in three steps, first in anomalous deposition by a current pulse, secondly by dissolution and oxidation during the open circuit potential in each cycle and finally by anodic stripping of the fully plated sample. The treatment leaves a stable phase with an alloy composition of Ni 0.8 Zn 0.2 . The potential-time curves during the plating procedure were used to qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
3
1
Order By: Relevance
“…The Ni 2p XPS region after Ni PCD (Figure b) shows characteristic peaks for metallic Ni at 851.7 and 868.9 eV with little or no oxide present . This contrasts with the previous work by Göransson et al, who report the presence of NiO and Ni­(OH) 2 species in their Ni PCD sample . We attribute this discrepancy to the difference in the PCD parameters: the work by Göransson et al used longer pulse durations and lower current density then what we applied in our study.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…The Ni 2p XPS region after Ni PCD (Figure b) shows characteristic peaks for metallic Ni at 851.7 and 868.9 eV with little or no oxide present . This contrasts with the previous work by Göransson et al, who report the presence of NiO and Ni­(OH) 2 species in their Ni PCD sample . We attribute this discrepancy to the difference in the PCD parameters: the work by Göransson et al used longer pulse durations and lower current density then what we applied in our study.…”
Section: Resultscontrasting
confidence: 95%
“…54 This contrasts with the previous work by Goransson et al, who report the presence of NiO and Ni(OH) 2 species in their Ni PCD sample. 55 We attribute this discrepancy to the difference in the PCD X-ray diffraction (XRD) of the Ni layer electrodeposited by PCD confirms the deposition of polycrystalline Ni (Figure 3d). This sample was prepared by 20 000 cycles of PCD on a Cu foil substrate to ensure sufficient thickness for the XRD experiment.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…The H 2 O 2 selectivity for H 2 O 2 production varied between 4% and 8% on Au NRs (Figure S8, Supporting Information) and was ≈40% on Ni (Figure S9, Supporting Information). Goransson et al also reported a low selectivity of ≈20% on Ni catalyst in the same electrolyte . Thus, the previously mentioned high selectivity of the prepared NRs can be attributed to the synergetic effect between Au and Ni via epitaxial growth.…”
mentioning
confidence: 82%
“…Among other transition metal-based systems (e.g. nickel, zinc and nickelrich NiZn alloys) [8], polycrystalline nickel electrodes have been the subject of extensive studies in acidic aqueous media [9][10][11][12][13][14][15], where dissolution and passivation processes are observed [16][17][18][19][20][21][22]. Both phenomena were postulated through reaction schemes which begin with two common electrochemical steps, reactions 1 and 2, where an intermediate Ni(II) species is produced from water adsorption on the metal surface.…”
Section: Introductionmentioning
confidence: 99%